Human taeniasis: current insights into prevention and management strategies in endemic countries - Okello A; Thomas LF (Dove Medical Press, 2017)
Anna L Okello,1 Lian Francesca Thomas2 1Division of Infection and Pathway Medicine, Edinburgh Medical School, Biomedical Sciences College of Medicine and Veterinary Medicine, University of Edinburgh, Scotland; 2Independent Consultant, Lusaka, Zambia Abstract: Human taeniasis is a zoonotic condition resulting from infection with the adult stages of Taenia saginata (“beef tapeworm”), Taenia solium (“pork tapeworm”) or Taenia asiatica (“Asian tapeworm”). Although these parasites have a worldwide distribution, the overwhelming burden is felt by communities in low- and middle-income countries. This is particularly true for T. solium, whereby infection of the central nervous system with the larval stage of the parasite (neurocysticercosis) is a major cause of acquired epilepsy in low-resource settings. With a focus on endemic countries, this review provides an insight into the prevention and management of human taeniasis, concluding with some recent case studies describing their implementation. Discussion of the opportunities and challenges regarding current fecal and serological diagnostic assays for detecting Taenia spp. highlights the importance of accurate and accessible diagnostic options for the field situation. The lack of long-term impact on the parasites’ lifecycle from human anthelmintic treatment, coupled with the propensity for adverse reactions, highlights the importance of a “two-pronged” approach that considers the relevant animal hosts, particularly in the case of T. solium. Aside from the therapeutic options, this review reiterates the importance of adequate assessment and consideration of the associated behavioral and policy aspects around sanitation, hygiene and meat inspection that have been shown to support parasite control, and potential elimination, in endemic regions. Keywords: Taenia solium, Taenia saginata, cysticercosis, zoonotic disease, neglected tropical diseases